New Method for Determination of Molybdenum(VI) through Flow Injection Analysis Via the Consumption of Liberated Oxygen from Reaction System Ammonia-Hydrogen peroxide-Molybdenum(VI) in the Presence of Pyrogallol - Baghdad Science Journal (مجلة بغداد للعلوم)
This piece of research work aims to study one of the most difficult reaction and determination due to continuous and rapid variation of reaction products and the reactants. As molybdenum (VI) aid in the decomposition of hydrogen peroxide in alkaline medium of ammomia, thus means a continuous liberation of oxygen which cuases and in a continuous manner a distraction in the measurement process. On this basis pyrogallol was used to absorbe all liberated oxygen and the result is an a clean undisturbed signals. Molybdenum (VI) was determined in the range of 4-100 ?g.ml-1 with percentage linearity of 99.8% or (4-300 ?g.ml-1 with 94.4%) while L.O.D. was 3.5 ?g.ml-1. Interferring ions (cations and anions) were studied and their main effect was reduced using mini column cataining resin, or the separation of molybdenum via its precipitation prior to injection. The reaction system and manifold were used to determine pyrogallol (4-40 ?g.ml-1, L.O.D. 80 ?M) and hydrogen peroxide (0.1-5M, L.O.D. 50 mM). Relative standard diviation was better the 1%.